1984
DOI: 10.1029/jb089ib06p04403
|View full text |Cite
|
Sign up to set email alerts
|

A discussion of impulses and jerks in the geomagnetic field

Abstract: French and United Kingdom workers have published reports describing a sudden change in the secular acceleration, called an impulse or a jerk, which took place in 1969. They claim that this change took place in a period of a year or two and that the sources for the alleged jerk are internal. This paper questions their method of analysis, pointing out that their method of piecemeal fitting of parabolas to the data will always create a discontinuity in the secular acceleration where the parabolas join and that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 15 publications
2
31
1
1
Order By: Relevance
“…Their methods, however, are subjective in the determination of the occurrence epochs of jerks, and the estimated jerk amplitudes may not be reliable as has been pointed out by, for example, Alldredge (1984). Stewart and Whaler (1995) and Alexandrescu et al (1995) developed the objective methods with the optimal piecewise regression analysis and the wavelet analysis, respectively, for determining the occurrence epochs of jerks.…”
Section: Statistical Time Series Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Their methods, however, are subjective in the determination of the occurrence epochs of jerks, and the estimated jerk amplitudes may not be reliable as has been pointed out by, for example, Alldredge (1984). Stewart and Whaler (1995) and Alexandrescu et al (1995) developed the objective methods with the optimal piecewise regression analysis and the wavelet analysis, respectively, for determining the occurrence epochs of jerks.…”
Section: Statistical Time Series Modelmentioning
confidence: 99%
“…Malin and Hodder (1982) evaluated the spherical harmonic coefficients from the third order time derivative of the geomagnetic annual means at 83 observatories, and concluded that the 1969 jerk is of internal origin. Alldredge (1984) and Alldredge (1985), however, questioned the data selection and the method of analysis by Malin and Hodder (1982), and insisted that an external current system could generate the observed jerks. Despite of many researches on the jerks, whether their sources are internal or external is still controversial (e.g., Kerridge and Barraclough, 1985;McLeod, 1985;Gavoret et al, 1986;Gubbins and Tomlinson, 1986;Thompson and Cain, 1987;Whaler, 1987;Golovkov et al, 1989;McLeod, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…6 and 7 (see also Demetrescu and Dobrica (2014)), the geomagnetic jerk might be seen as a result of a more general phenomenon, namely the evolution of the secular variation as a result of a superposition of two (or several) waves describing effects of processes in the Earth's core at two (or several) time-scales. This is in line with Bloxham et al (2002) and Alldredge (1984;1985) arguments and, respectively, on geometric arguments. Finlay and Jackson (2003) and Jackson and Finlay (2007) have identified core surface equatorial westward moving magnetic flux patches that can be either a result of core flow vortices entrained by a larger scale westward flow, or Alfvén waves excited in the core.…”
Section: Observatory Datamentioning
confidence: 51%
“…At Trivandrum, Annamalainagar and Kodaikanal, the initial datum may be unreliable since all were extrapolated from 1958 (see Alldredge, 1984, for example, for a discussion about such errors). The difference appears to be declining in the last decade (1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990).…”
Section: Comparison Of the Observed Annual Mean Values With Igrf Modelsmentioning
confidence: 99%